Culture Throughlines - Banfield, William (Smithsonian Institution Scholarly Press, 2024)
Cultural throughlines delineate the ways in which contemporary artistry, new works, and creative methods can be appreciated and seen as a “tri-vision tradition” (then, now, and when) as they tie into cultural linkages from our past and suggest our future. What is new are today’s social languages, platforms, movements, and fluidity, all of which lead to discussions that anticipate ever-changing cultural shifts and create dialogue about cultural practices. It’s about living and how we do culture: what it is, what it means, and why. Questions arise about what we as artists value (identity, creative voice, survival). How do we get there? And what do everyday people value and care about?